A novel method to synthesize stable nitrogen-rich polynitrobenzenes with π-stacking for high-energy-density energetic materials. Issue 73 (24th August 2018) - Yang, Xiaoming; Lin, Xinyu; Yang, Li; Zhang, Tonglai
Abstract : A larger multi-nitro, multi-azide and multi-oxidized furazan ring compound with π–π stacking is herein reported. The coupling reaction of a NN bond and an azido was an efficient method to synthesize benzotriazole. Abstract : Two nitrogen-rich energetic compounds with π-stacking, 1, 1′-dichloro-2, 2′, 3, 3′, 6, 6′-hexanitro-5, 5′-dihydroxyazobenzene (1 ) and 8-(2, 4, 6-triazido-3, 5-dinitrophenyl)-8 H -[1, 2, 3]triazolo[4′, 5′:5, 6]benzo[1, 2- c :3, 4- c ′]bis([1, 2, 5]oxadiazole) 1, 4-dioxide (2 ), were prepared by a novel synthesis method, and their structures were determined by single-crystal X-ray diffraction analysis. The decomposition temperature of1 is 336 °C and2 exhibits excellent heat of formation of 1160.5 kJ mol −1 (2.21 kJ g −1 ). The condensation reaction of the coupling of a NN bond and an azido from1 to2 was proved to be an efficient method to synthesize benzotriazole. This synthetic strategy for benzotriazole may arouse considerable interest in the area of organic synthesis.